Rifampicin can induce antibiotic tolerance in mycobacteria via paradoxical changes in rpoB transcription - Jun-Hao Zhu (Nature Portfolio, 2018)
The antibiotic rifampicin inhibits transcription by targeting RpoB, a bacterial RNA polymerase subunit. Here, Zhu et al. show that certain cells in mycobacterial populations can continue to grow and divide in the presence of rifampicin due, paradoxically, to rifampicin-induced upregulation of the rpoB gene.